Metals from USCGC Healy cruise HLY1202 from the Arctic, North of Alaska in 2012 (OA - Canada Basin project) - Dr Bogdan Onac (Biological and Chemical Oceanography Data Management Office (BCO-DMO), 2014)
USGS Arctic Ocean Carbon Cruise 2012: Metals Data Trace metal data from the HLY 1202 cruise For aditional information see: HLY1202 Cruise Report, Appendix E U.S. Geological Survey Data Series 862 - Methods